Transformation of Newspapers’ Thematic Structure in the 20th Century: A Comparative Analysis of Estonia, Finland and Russia - Lõhmus, Maarja; Nieminen, Hannu; Kõuts, Ragne; Kõnno, Andres; Aljas, Agnes (Javnost-The Public, 2013)
This article focuses on the thematic structure and contextualisation of the future in the main daily newspapers of the three neighbouring countries of Finland, Estonia and Russia throughout the 20th century. We mapped the content of 2079 Finnish, 2242 Estonian and 1723 Russian daily newspaper articles. The Finnish Helsingin Sanomat concentrated on the issue of “state and legislation”; the second most common topic in the Finnish sample was economics, at about 20 percent of the articles, with the exception of the 1910s and 1930s. In Estonia we did not find any dominant topic during the 20th century; there were many different topics related to the agenda. Politics and governance and related issues were particularly dominant during the periods of independence. Economy-related issues were more or less dominant during the period of Soviet occupation. The topics of economics and human relations and values were dominant in the Russian Pravda throughout the 20th century. The analysis reveals that Finnish media were more diverse than Estonian and Russian, which displayed a lack of diversity especially during the Communist period.